The Effect of Customer Experience and Brand Image on Customer Loyalty with Mediation of Customer Satisfaction in the Culinary Industry - Yudantri, Anindya Sukma; Widodo, Arry; Rubyanti, Nurafni; Silvianita, Anita (PT FORMOSA CENDEKIA GLOBAL, 2025)
Indonesia's culinary industry is experiencing rapid growth, driven by people's increasing interest in food trends and the eating out lifestyle. One trend that is attracting attention is the consumption of spicy food, which is growing thanks to social media challenges with extreme levels of spiciness. In an increasingly fierce competition, business strategies based on customer experience, brand image, and customer satisfaction are key factors in increasing customer loyalty. This study shows that while customer experience contributes to satisfaction, the relationship does not directly guarantee loyalty. Other factors, such as taste and facilities, still play an important role in building competitiveness in the culinary industry.